Does the Simultaneous Introduction of Several Pharmaceuticals in the Post-Lenalidomide Era Translate to Better Outcomes in Relapse Refractory Multiple Myeloma? Findings from the Real-World Innovation in Multiple Myeloma (REAL IMM) Study - Petrakis, Ioannis; Kontogiorgis, Christos; Nena, Evangelia; Delimpasi, Sosana; Loutsidi, Natasa E.; Spanoudakis, Emmanouil; Intzes, Stergios; Misidou, Christina; Symeonidou, Marianthi; Giannakoulas, Nikolaos; Constantinidis, Theodoros C.; Terpos, Evangelos (Cancers, 2023)
Newer methodologies are needed to assess the real-world comparative effectiveness of a “generation” of pharmaceutical innovation versus the prior standard of care. This chart review study aimed to first evaluate the cumulative clinical benefits of pharmaceutical innovation in everyday relapse/refractory multiple myeloma before analyzing findings in the context of respective real-world outcomes from the bortezomib/lenalidomide era. Study endpoints included the 52-week PFS rate in second and third line of therapy (LOT), mPFS-2 across the first and second LOT, the ORR, reasons for discontinuation, and the treatment duration per therapeutic algorithm. Data from 107 patients were collected. The median follow-up was 2.0 years. Of the subjects who met the selection criteria for the second LOT, 72.2% maintained the PFS at 52 weeks. In the third-line setting, the PFS rate at 52 weeks was 63.5%. The mPFS across the first and second, the second, and the third LOTs were 26, 17, and 15 months, respectively. The ORR was 76.1% in the second and 69.7% in the third LOT. After non-response or progression, the main reason for drug discontinuation was treatment intolerability. The second-line ORR and the 52-week PFS rate were similar to previous real-world findings from the bortezomib/lenalidomide era. The cumulative mPFS across the second and third LOTs was higher than the respective mPFS across the first and second LOTs. Despite its limitations, the methodology and findings from this study may be used in future clinical and economic evaluations across all hematological malignancies.